Flagship enterprises, entrepreneurial clusters, and business entry rates : insights from the knowledge spillover theory of entrepreneurship - Anokhin, Sergey; Chistyakova, Natalia; Antonova, Irina; Spitsina, Lyubov; Wincent, Joakim; Parida, Vinit (Taylor & Francis, 2021)
Employing a panel setting of 88 counties in the State of Ohio over the five-year period ending in 2006, this study aims to investigate the applicability of the knowledge spillover theory of entrepreneurship in explaining the relationships between flagship enterprises, entrepreneurial clusters, and business entry rates. The study confirms the overall positive relationship between flagship enterprises and startup rates, and the negative relationship between entrepreneurial clusters and startup rates. It further demonstrates that the effect of clusters is moderated by local unemployment rates so that higher rates of unemployment weaken the negative impact of entrepreneurial clusters on startup rates. Based on the evidence collected, policy makers should increase support for flagship enterprises in their regions, and would-be business owners should consider locating their ventures in proximity to flagship companies.
Keywords: Flagship enterprises; entrepreneurial clusters; knowledge spillover theory of entrepreneurship; business entry rates; fi=Strateginen johtaminen|en=Strategic Management|